Mechanistic degradation analysis and impacts of passivation interlayer and device packaging towards long term stability of printed perovskite solar cells - Aw, Yeow Chong (Nanyang Technological University, 2020)
As the 3rd generation photovoltaic (PV) technology in the PV arena, perovskite solar cells (PSCs) have been widely investigated by researchers all around the world due to its flexibility of tuning different compositions fitting into the three-dimensional ABX3 structure. Thanks to the materials’ excellent optoelectronic properties, state of the art of PSCs currently feature power conversion efficiencies (PCEs) comparable to the widely used silicon-based PV technologies, which is attained within a period of only 10 years of research. Having said that, one of the biggest issues with perovskite solar cells is their stability, (e.g. toward moisture, oxygen and heat), which holds back PSCs technology from commercialisation. Therefore, increasing amount of effort has been channelled to improve the stability of PSC. This research project focuses on employing a two-pronged approach to boost the stability of slot die-coated (“printed”) perovskite solar cells towards both moisture and heat. Firstly, a fluorinated passivation interlayer is inserted between the perovskite and hole transport layers. The passivator increased the hydrophobicity profile of perovskite films, which reduces the chance of moisture ingression, evident from much more enhanced storage and operational stability under 1 sun condition, relative to those pristine cells without treatment. More importantly, the presence of the passivation layer was also found to enhance Voc and PCE of the devices, suggesting the performance of the devices are not compromised after adding the passivation layer. Secondlt, this project also focuses on comparing three different types of encapsulant, namely ethylene vinyl acetate (EVA), polyolefin elastomer (POE) and polyisobutylene (PIB). Due to its much lower water vapour transmission rate (WVTR) and more extended lamination temperature range, PIB encapsulant standout as the overall encapsulated device efficiency and stability surpassed those of EVA and POE-encapsulated devices. In comparison to the unencapsulated devices, PIB-encapsulated devices feature much longer the T90s (the time it takes for the device to reach 90% of the initial efficiency) upon thermal stress at 65oC and 85oC. Particularly, a remarkable T90 of 1000 hours for encapsulated devices heated at 65oC. This shows that encapsulation does help in prolonging the degradation period of perovskite solar cells. From mechanism point of view, it is believed that PIB encapsulant is able to prevent out-gassing of decompression products that occurred due to heating, which in turns reduces the rate of degradation of the perovskite layer. Our work presents a major proof of demonstration that perovskite solar cells can be stabilized against external stressors such as moisture and heat.